The symbolic reach of the Catholic Church: liturgy-based language among atheists and Catholics in Poland. Issue 2 (3rd April 2017) - Kamasa, Victoria
ABSTRACT: The power of the Catholic Church in Poland can be seen throughout modern Polish history. It can also be observed in the influence of the Catholic clergy on political and social life in Poland. But how far-reaching is this power? Does it only concern the Catholic majority in Polish society or does it extend also to the atheist minority? In this article, we address this question through a study of the linguistic habitus of two groups (Polish Catholics and Polish atheists), specifically an analysis of conceptual metaphors in a corpus compiled from web forums. We examine the frequencies of three metaphors concerning love, death and sin previously identified in Catholic transition rituals, such as baptisms or weddings. The results show no quantitative differences in the usage of these metaphors and instead significant qualitative similarities in the language form of the metaphors. The findings thus suggest the ability of the Catholic Church to influence the ways of speaking and possibly also of thinking and acting among both Catholics and atheists in Poland.